2015
DOI: 10.1002/2015gl065961
|View full text |Cite
|
Sign up to set email alerts
|

The competition of electron and ion heating during magnetic reconnection

Abstract: The physical processes that control the partition of released magnetic energy between electrons and ions during reconnection is explored through particle‐in‐cell simulations and analytical techniques. We demonstrate that the development of a large‐scale parallel electric field and its associated potential controls the relative heating of electrons and ions. The potential develops to restrain heated exhaust electrons and enhances their heating by confining electrons in the region where magnetic energy is releas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
90
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 27 publications
12
90
0
Order By: Relevance
“…The heating is in a good agreement with the analytical estimate: ΔT (i) ∼ m i V 2 A(up) ∼ 0.2 for ∼ 0.1 [Haggerty et al, 2015]. The global evolution of the magnetic reconnection (reconnection rate and Hall fields) is nearly unchanged in the presence of cold ions and depends on upstream parameters (B and n).…”
Section: Discussionsupporting
confidence: 79%
“…The heating is in a good agreement with the analytical estimate: ΔT (i) ∼ m i V 2 A(up) ∼ 0.2 for ∼ 0.1 [Haggerty et al, 2015]. The global evolution of the magnetic reconnection (reconnection rate and Hall fields) is nearly unchanged in the presence of cold ions and depends on upstream parameters (B and n).…”
Section: Discussionsupporting
confidence: 79%
“…They implicitly assume the localtype Speiser motion, while the relevant self-consistent orbits have not been investigated. In fact, Haggerty et al 21 showed in Figure 2(d) of their paper that the electron jet region, flanked by the bipolar E k layers, extends 40d i 's away from the X-line. This is favorable for the noncrossing electrons.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Second, the electron heating mechanisms have been actively studied in the last few years. 21,43,51 These works reported electrons parallel heating outside the ECL inside the outflow exhaust. They implicitly assume the localtype Speiser motion, while the relevant self-consistent orbits have not been investigated.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…We propose the following explanation: in order for a charged particle to accelerate multiple times, it must propagate upstream against the Alfvénic outflow that ejects plasma β ≪ 1, reconnection heats electrons to an appreciable fraction of the available magnetic energy density 47,48 : ∆T e ≈ 0.03m e c 2 Ae , corresponding to v th,e /c A ≈ 0.06m i /m e ≈ 10 so that essentially all reconnection-heated electrons will satisfy the criterion, independent of the initial temperature. In contrast, ions are typically sub-Alfénic and would require an injection mechanism (e.g.…”
Section: An 'Injection Criterion' For Enhanced Accelerationmentioning
confidence: 99%